2021
DOI: 10.3390/s21144672
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Enzymatic and Non-Enzymatic Electrochemical Glucose Sensing

Abstract: The detection of glucose is crucial in the management of diabetes and other medical conditions but also crucial in a wide range of industries such as food and beverages. The development of glucose sensors in the past century has allowed diabetic patients to effectively manage their disease and has saved lives. First-generation glucose sensors have considerable limitations in sensitivity and selectivity which has spurred the development of more advanced approaches for both the medical and industrial sectors. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
124
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(124 citation statements)
references
References 215 publications
(354 reference statements)
0
124
0
Order By: Relevance
“…Figure 3 a shows the CV of the glucose sensor at pH 7, exhibiting no oxidation-reduction peaks. Similar studies have been carried out exploring the effect of the pH on the electrode sensitivity, revealing that the catalyst sensitivity to glucose is boosted by increasing the pH [ 45 , 46 , 47 ]. The reduced species transferred the excess electrons to the Ni 2+ /Ni 3+ redox couple leading to an enhancement in the redox current.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Figure 3 a shows the CV of the glucose sensor at pH 7, exhibiting no oxidation-reduction peaks. Similar studies have been carried out exploring the effect of the pH on the electrode sensitivity, revealing that the catalyst sensitivity to glucose is boosted by increasing the pH [ 45 , 46 , 47 ]. The reduced species transferred the excess electrons to the Ni 2+ /Ni 3+ redox couple leading to an enhancement in the redox current.…”
Section: Resultsmentioning
confidence: 91%
“…The reduced species transferred the excess electrons to the Ni 2+ /Ni 3+ redox couple leading to an enhancement in the redox current. It is worth mentioning that ion contamination limitation can be eliminated employing alkaline conditions on the electrode surface, as the hydroxyl groups (OH¯) suppress the chloride (Cl¯) adsorption to the electrode surface [ 45 , 47 ]. Accordingly, changing the real pH of the sweat solution in this work significantly enhanced the sensitivity of the as-prepared electrode.…”
Section: Resultsmentioning
confidence: 99%
“…According to a recent review study by [ 26 ], the advancements of BioSS/NanoBioSS are fast attaining remarkable attention in the biomedical/clinical/healthcare fields due to their wide-ranging applications. BioSS/NanoBioSS are presently been efficaciously employed for detecting and diagnosing, treatment of diseases, as well as in the monitoring and management of human health [ 26 , 95 , 154 158 ]. Hence, there should be incessant advances in the development of materials (NMs to be specific) for the fabrication of BioSS/NanoBioSS.…”
Section: Bioss/nanobioss For the Detention And Treatment Of Diseasesmentioning
confidence: 99%
“…Indeed, the in vivo study showed that L. multiflora reduced blood glucose levels very significantly in treated mice as shown in Figure 13. The enzyme glucose oxidase plays an important role in basic research as a biosensor (Hassan et al, 2021;Hyo et al, 2020;Stefano et al, 2011). In this study, this enzyme was used to develop a UV-visible spectrophotometric method for screening plants with anti-diabetic properties.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%